2016
DOI: 10.1038/srep18757
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion model for the coordination of DNA replication in Schizosaccharomyces pombe

Abstract: The locations of proteins and epigenetic marks on the chromosomal DNA sequence are believed to demarcate the eukaryotic genome into distinct structural and functional domains that contribute to gene regulation and genome organization. However, how these proteins and epigenetic marks are organized in three dimensions remains unknown. Recent advances in proximity-ligation methodologies and high resolution microscopy have begun to expand our understanding of these spatial relationships. Here we use polymer models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Heterochromatin is characterized by the strong suppression of foreign gene expression and enriched in H3K9me2 and H3K9me3. As in metazoans, heterochromatin in S. pombe is localized at the periphery of the nucleus or nucleolus as predicted from polymer models (Pichugina et al ., ). It was commonly believed that silent heterochromatin is highly condensed and excludes transcription factors from accessing DNA, as in metazoans.…”
Section: Higher‐ordered Structures Of Chromatin Domainsmentioning
confidence: 97%
See 1 more Smart Citation
“…Heterochromatin is characterized by the strong suppression of foreign gene expression and enriched in H3K9me2 and H3K9me3. As in metazoans, heterochromatin in S. pombe is localized at the periphery of the nucleus or nucleolus as predicted from polymer models (Pichugina et al ., ). It was commonly believed that silent heterochromatin is highly condensed and excludes transcription factors from accessing DNA, as in metazoans.…”
Section: Higher‐ordered Structures Of Chromatin Domainsmentioning
confidence: 97%
“…Direct measurements of physicochemical properties of chromosomes also provide insights into the nuclear organization of the chromosomes. Polymer models of chromosomes have also been used for predicting biologically relevant properties of chromosomes (Tanizawa et al ., ; Grand et al ., ; Gong et al ., 2015; Pichugina et al ., ). Combinations of these techniques will provide new insights into the temporal and spatial organization of the nucleus during biological processes.…”
Section: Perspectivesmentioning
confidence: 97%
“…The spatio-temporal model simulates DNA replication at a whole-genome level and is tailored to the case of fission yeast, exploiting recent three-dimensional genome structures derived by chromosome conformation capture experiments [43,57]. A graphical summary of the model is given in Fig.…”
Section: A Stochastic Three-dimensional Model Of Dna Replicationmentioning
confidence: 99%
“…In budding yeast nuclei, early firing origins were found to be clustered [42]. A recent study in fission yeast identified a gradient of origin efficiency centered on the spindle pole body (SPB), suggesting a diffusion-based mechanism coordinating DNA replication [43].…”
Section: Introductionmentioning
confidence: 99%
“…A proposed mechanism for epigenetic inheritance is that the association of H3K9 methyltransferases with replicative polymerases would facilitate the modification of newly deposited nucleosomes with marks specific for the replicated region, as might also be the case for other modifications (19)(20)(21)(22). Such associations have indicated that replication control could be important for the chromatin domain organization of chromosomes by restricting the spreading of modifying enzymes to specific regions, either in 2D along the chromatin fiber or perhaps in 3D, through the coregulation of replication origins or forks occupying a common subnuclear compartment (23).…”
mentioning
confidence: 99%